Via di accesso innovativa alla lamina quadrilatera: Anterior Combined Endopelvic (ACE) approach - Rocca, G.; Bolcic, S.; Patronis, D.; Boero, E. (Lo Scalpello - Journal, 2018)
ACE APPROACH: INNOVATIVE APPROACH TO THE QUADRILATERAL LAMINAWe have designed and performed a new anterior pelvic approach for eight years. This has enabled us to obtain a widedirect visibility, and to improve our clinical and functional outcomes. Being easy to perform, it allows for reduction ofsurgical times. The learning curve is quicker, therefore it is intended to be an opportunity for those young surgeonswho want to undertake this rather complex surgery.